The Desired Image of the Future Economy of the Industrial Region: Development Trends and Evaluation Methodology - Romanova, Olga Aleksandrovna; Sirotin, Dmitry Vladimirovich (Economy of Regions, 2017)
In the article, the authors emphasize that industrial regions play an important role in the increasing of technological independence of Russia. We show that the decline in the share of processing industries in the gross regional product can not be treated as a negative de-industrialization of the economy. The article proves that the increase in the speed of changements, instability of socio-economic systems, the diverse risks predetermine the need to develop new methodological approaches to predictive research. The studies aimed at developing a technology for the design of the desired image of the future and the methodology for its evaluation are of high importance. For the initial stage of the research, the authors propose the methodological approach for assessing the desired image of the future of metallurgy as one of the most important industry of the region. We propose the term of «technological image of the regional metallurgy». We show that repositioning the image of the regional metallurgical complex is quite a long process. This have determined the need to define the stages of repositioning. The proposed methodology of the evaluation of desired future includes the methodological provisions to quantify the characteristics of goals achieved at the respective stages of the repositioning of the metallurgy. The methodological approach to the design of the desired image of the future implies the following stages: the identification of the priority areas of the technological development of regional metallurgy on the basis of bibliometric and patent analysis; the evaluation of dynamics of the development of the structure of metal products domestic consumption based on comparative analysis and relevant analytical methods as well as its forecasting; the design of the factor model, allowing to identify the parameters quantifying the technological image of the regional metallurgy based on the principal components method,; systematization of predicted values of the parameters defining the stages of repositioning and designing the new technological image of the regional metallurgy; the development of mathematical model for the recognition of the technological image of a regional metallurgy on the basis of neural networks.